2013
DOI: 10.1021/ic400491q
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of Endohedral Amine-Functionalized Bis(phosphine) Pt(II) Complexes as Models for Emissive Metallacycles

Abstract: The photophysical properties of bis(phosphine) Pt(II) complexes constructed from 2,6-bis(pyrid-3-ylethynyl) aniline and 2,6-bis(pyrid-4-ylethynyl) aniline vary significantly, even though the complexes differ only in the position of the coordinating nitrogen. By capping the ligands with an aryl bis(phosphine) Pt(II) metal acceptor, the photophysical properties of the two isomeric systems were directly compared, revealing that the low-energy absorption and emission bands of the two systems were separated by 30 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
3
13
0
Order By: Relevance
“…Our recent measurements of the fluorescence lifetimes of related model complexes, wherein a ligand is capped by two Pt centers, gave lifetimes on the order of 1-2 ns. These lifetimes are similar to those of the free ligands, suggesting that ligand-centered excited states are responsible for the observed emission (41).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Our recent measurements of the fluorescence lifetimes of related model complexes, wherein a ligand is capped by two Pt centers, gave lifetimes on the order of 1-2 ns. These lifetimes are similar to those of the free ligands, suggesting that ligand-centered excited states are responsible for the observed emission (41).…”
Section: Resultssupporting
confidence: 62%
“…Moreover, recent reports have demonstrated that platinum-based SCCs can act as effective hosts for guests and have interesting photophysical properties (37)(38)(39)(40)(41)(42). In particular, highly emissive rhomboids based on aniline-containing donors and Pt-based metal acceptors have…”
mentioning
confidence: 99%
“…[21][22]24 The effect of the second coordination sphere on catalytic reactions, 22 tandem catalysis 25 and spectroscopic cooperativity effects can also be studied. [26][27][28][29] For several applications it is important to control the size of the sphere that is formed during the assembly process, but this can be challenging. Key parameters for selective palladium-based systems have been identified previously by the group of Fujita.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24]31 The analogous platinum systems display superior stability under a variety of conditions including the presence of coordinating substrates, due to the stronger and kinetically more stable Pt-N(pyridine) bonds. 24 Moreover, platinum-spheres are less prone to degradation by reducing agents 23 and display good fluorescent properties, [26][27][28][29] making them promising candidates for biological applications. [32][33] Research has been focused mainly on the formation of palladiumbased systems [34][35][36][37] and their application across the fields.…”
Section: Introductionmentioning
confidence: 99%
“…SCCs can employ rigid organic ligands as structural linkers, and these organic linkers can be usually modified with functional groups that can be meticulously chosen not to interfere with self-assembly process. Once the structures are formed, these functional groups can provide opportunities to impact unique properties that are relative to the functionalized materials 21 29 30 31 32 33 34 35 . That is to say, SCCs with promising light-harvesting or electronic properties will have possibilities to improve the performance of DSSCs 36 .…”
mentioning
confidence: 99%